PEMANFAATAN CERITA RAKYAT SEBAGAI PENANAMAN ETIKA UNTUK MEMBENTUK PENDIDIKAN KARAKTER BANGSA - Kristanto, M. (Universitas Pendidikan Indonesia, 2014)
Folklore that are emerging in various regions in Indonesia have ethical moral values that are beneficial to the formation of a golden generation of Indonesia. Folklore when inherited or inculcated into children early on will equip students motor and psychomotor development, especially in students' character membangan early winning personality. Planting of ethics is intended to form a person's character that leads to positive things. Planting good ethics can certainly build character, attitudes, and behaviors that reinforce soft skills to instill good habits. Utilization of folklore that there are very effective to teach ethics and good morals. Through the characters in the story can be conveyed attitudes, behaviors, and said words that reflect the character and moral ethics. In the story reflected the presence of noble values, among others, honesty, cooperation, hard work, responsibility, religion. These values can be used as a means of character education.Keywords: folklore, values, ethics, character education.